2018
DOI: 10.1136/archdischild-2018-315342
|View full text |Cite
|
Sign up to set email alerts
|

Randomised cross-over study of automated oxygen control for preterm infants receiving nasal high flow

Abstract: ObjectiveTo evaluate a prototype automated controller (IntellO2) of the inspired fraction of oxygen (FiO2) in maintaining a target range of oxygen saturation (SpO2) in preterm babies receiving nasal high flow (HF) via the Vapotherm Precision Flow.DesignProspective two-centre order-randomised cross-over study.SettingNeonatal intensive care units.PatientsPreterm infants receiving HF with FiO2 ≥25%.InterventionAutomated versus manual control of FiO2 to maintain a target SpO2 range of 90%–95% (or 90%–100% if FiO2=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 17 publications
5
44
0
1
Order By: Relevance
“…Sixteen single or multicentre clinical studies have been undertaken comparing closed loop automated oxygen control to manual oxygen control in neonates to determine whether automating FiO 2 control was associated with a greater target SpO 2 achievement. They consistently demonstrated that closed loop automated oxygen control maintained the patient within their target SpO 2 range a significantly greater proportion of the time than manual control . Closed loop automated oxygen control has been demonstrated to reduce hyperoxic episodes, in one study almost halving the frequency (9.3 to 4.7 episodes per 90 minutes) and the duration (19.3 s‐10.1 s) of hyperoxic episodes and in another study reducing the median percentage time spent with an SpO 2 > 95% from 41.9% to 19.3% ( P < .001) .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Sixteen single or multicentre clinical studies have been undertaken comparing closed loop automated oxygen control to manual oxygen control in neonates to determine whether automating FiO 2 control was associated with a greater target SpO 2 achievement. They consistently demonstrated that closed loop automated oxygen control maintained the patient within their target SpO 2 range a significantly greater proportion of the time than manual control . Closed loop automated oxygen control has been demonstrated to reduce hyperoxic episodes, in one study almost halving the frequency (9.3 to 4.7 episodes per 90 minutes) and the duration (19.3 s‐10.1 s) of hyperoxic episodes and in another study reducing the median percentage time spent with an SpO 2 > 95% from 41.9% to 19.3% ( P < .001) .…”
Section: Resultsmentioning
confidence: 94%
“…A crossover study found that with automated weaning, infants spent significantly more time with a FiO 2 < 0.25 than with manual control . A further crossover study of automated FiO 2 control versus manual control in infants on nasal cannula oxygen found that, in addition to automated control resulting in a significantly greater proportion of time with saturations within the target range, the automated control also tended to result in a FiO 2 of 21%, whereas manual control resulted in an FiO 2 of 30% . Those results suggest automated control might identify, which patients no longer require supplementary oxygen more quickly.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Machines have been developed that use regular pulse oximetry measurements to modify delivered oxygen concentration automatically to maintain Sp0 2 in the recommended target range (90–95%). Two UK units randomised 30 infants (gestation 24–27 weeks, weight 959–1443 g, age 18–53 days) receiving high‐flow oxygen with Fi0 2 ≥ 25% to commence either manual or automatic control of Fi0 2 . The automatic device, called an Intell0 2 , was set to maintain an Sp0 2 of 93%.…”
mentioning
confidence: 99%